O campo é cheio de coisas bonitas, pássaros, borboletas, flores, e a cidade só tem humanos e coisas que o humano constrói: representações sociais de campo, cidade, rural e urbano de alunos e professores da escola municipal 13 de maio, Upanema/RN - Silva, Ranielly Leticia da (Universidade Federal Rural do Semi-Árido, 2018)
This research investigates the Social Representation of the Countryside, the City, the Rural and the Urban concerning students, former and current teachers and the principal from a public municipal school from Upanema-RN. This study was carried out with students of 5th grade of Elementary School (first years); 6th and 7th grade of Elementary School (last years) from Escola Municipal 13 de Maio, besides teachers from that school. The main objective was to identify what are the social representations that those subjects have about the Countryside, the City, the Rural and the Urban, analyzing similarities and differences and understanding the relation between Countryside, City, Rural and Urban from the perspective of rural education. Besides that, we seek to understand what teachers from that school understand of Countryside, City, Rural and Urban, and if those perceptions interfere in their professional performance. Methodologically, we carried out bibliographic studies and field research, application of questionnaires and semi structured interviews. The research showed that people still relate the conception of delay to the Countryside, while the City is seen as modern, advanced and developed; on the other hand, City receives negative qualities, as violent and polluted, while Countryside receives qualities of calm/quiet; besides that, the researched subjects do not recognize Rural e Urban as dynamics that constitute those two places, but as an extension/continuation or even as the same thing (Countryside and City). Therefore, there is a need and importance to discuss those categories in a non-dichotomy way through works with the theory of Social Representation, aiming to demystify the idea related to the dimension of people life, mainly the one that relates Countryside to Delay.
Monografia
Keywords: Representações sociais; Educação do campo; Cidade/urbano; Campo/rural; Social representations; Rural education; Rural/urban; Countryside/city; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL